Simulasi Skenario Penutupan Lahan untuk Melihat Kondisi Hidrologi di Das Lisu, Kabupaten Barru - Samsul Labaco; Usman Arsyad; Anwar Umar (Jurnal Hutan dan Masyarakat, 2019)
The disruption of hydrological cycle will reduce watershed's ability to store water, so that discharge in dry season decreases and discharge in rainy season increases. These problems are caused by changes in land cover from forested land to non-forested. This study aims to develop a scenario for land cover planning that should be applied in the Lisu Watershed, Barru Regency. This study is mapping based on non-experimental research. The data obtained were analyzed spatially by overlay method. The Soil Water Assessment Tool (SWAT) model is used in preparation of land cover planning scenarios to predict hydrological conditions. The results showed that scenario 2, namely land cover planning based on the district space map pattern is the best scenario. Addition of forest area to 61.60% resulting in the lowest yield of 3461.54 mm/year and 1519.53 mm/year. While the infiltration value produced is the highest infiltration value, which is 2299.20 mm/year.